Inspiratory threshold loading negatively impacts attentional performance - Kelley, Eli F.; Cross, Troy J.; Johnson, Bruce D. (Frontiers in Psychology, 2022)
Rationale: There are growing concerns over the occurrence of adverse physiologic events (PE) occurring in pilots during operation of US Air Force and Navy high-performance aircraft. We hypothesize that a heightened inspiratory work of breathing experienced by jet pilots by virtue of the on-board life support system may constitute a “distraction stimulus” consequent to an increased sensation of respiratory muscle effort. As such, the purpose of this study was to determine whether increasing inspiratory muscle effort adversely impacts on attentional performance. Methods: Twelve, healthy participants (age: 29 ± 6 yr) were recruited for this study. Participants completed 6 repetitions of a modified Masked Conjunctive Continuous Performance Task (MCCPT) protocol while breathing against 4 different inspiratory threshold loads to assess median reaction times (RT). A computer-controlled threshold loading device was used to set the inspiratory threshold loads. Repeated measures analysis of variances (ANOVAs) were performed to examine: (i) the efficacy of the threshold loading device to impose significantly higher loading at each loading condition; (ii) the effects of loading condition on respiratory muscle effort sensation; and (iii) the influence of hypercapnia on MCCPT scores during inspiratory threshold loading. Generalized additive mixed effects models (GAMMs) were used to examine the potential nonlinear effects of respiratory muscular effort sensation, device loading, and hypercapnia, on MCCPT scores during inspiratory threshold loading. Results: Inspiratory threshold loading significantly augmented (P < 0.05) inspiratory effort sensation and the inspiratory pressure-time product (PTP). Our analyses also revealed that median hit reaction time (RT) was positively associated with inspiratory effort sensation during inspiratory loading trials. Conclusion: The findings of this work suggest that it was not increasing inspiratory muscle effort (i.e., PTP) per se, but rather participant’s subjective perception of inspiratory “load” that impacts negatively on attentional performance; i.e., as the degree of inspiratory effort sensation increased, so too did median hit RT. As such, it is reasonable to suggest that minimizing inspiratory effort sensation (independent of the mechanical output of the inspiratory muscles) during high-performance flight operations may prove useful in reducing pilot RTs during complex behavioral tasks.